Do Internal Control and Compensation Matters in Fraud at Local Government? Information Foraging Perspective - Irwansyah Irwansyah; Indah Oktari Wijayanti; Septin Eka Putri (JAFFA, 2023)
Accounting fraud is still a problem in organizations, especially in the public sector. This research aims to provide empirical evidence of the influence of internal control of assets, information asymmetry, good government governance implementation, and compensation suitability on accounting fraud. Purposive sampling was the sample selection technique used, and obtained 70 respondents were finance employees in 39 Local Government Agencies in Bengkulu City. Data collected through distributing questionnaires was tested using multiple linear regression analysis. The results of the research show that internal control of assets, information asymmetry, and compensation suitability have a positive effect on accounting fraud in Bengkulu City's Local Government Agency. Good government governance implementation does not affect accounting fraud in the Local Government Agency in Bengkulu City. Accounting fraud mitigation can be enforced through several mechanisms, such as employee rotation and reducing information asymmetry in Bengkulu City Local Government Agencies.